2021
DOI: 10.3390/molecules26113389
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Attributes of Endocannabinoid System against Neuro-Inflammatory Autoimmune Disorders

Abstract: In humans, various sites like cannabinoid receptors (CBR) having a binding affinity with cannabinoids are distributed on the surface of different cell types, where endocannabinoids (ECs) and derivatives of fatty acid can bind. The binding of these substance(s) triggers the activation of specific receptors required for various physiological functions, including pain sensation, memory, and appetite. The ECs and CBR perform multiple functions via the cannabinoid receptor 1 (CB1); cannabinoid receptor 2 (CB2), hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 275 publications
(398 reference statements)
0
5
0
Order By: Relevance
“…The endocannabinoid system (ECS) modulates many physiological processes, including the cardiovascular, gastrointestinal and immune systems, pain, learning, memory, perception, mood, appetite, metabolism, emotions, and sleep [22,112,113,[277][278][279][280][281][282][283][284][285]. The bioactive endocannabinoid lipid mediators have potent anti-inflammatory activities [286][287][288][289][290][291]. In addition, they promote neural progenitor cell proliferation and differentiation, and have neuroprotective effects [20,[292][293][294].…”
Section: Endocannabinoidsmentioning
confidence: 99%
“…The endocannabinoid system (ECS) modulates many physiological processes, including the cardiovascular, gastrointestinal and immune systems, pain, learning, memory, perception, mood, appetite, metabolism, emotions, and sleep [22,112,113,[277][278][279][280][281][282][283][284][285]. The bioactive endocannabinoid lipid mediators have potent anti-inflammatory activities [286][287][288][289][290][291]. In addition, they promote neural progenitor cell proliferation and differentiation, and have neuroprotective effects [20,[292][293][294].…”
Section: Endocannabinoidsmentioning
confidence: 99%
“…PPARβ/δ-mediated glucose regulation is different from that of PPARγ; however, PPARβ/δ and PPARγ both are implicated in fiber distribution in the skeletal muscle, metabolism of glucose in the liver and controlling pancreatic islet cells function [53]. In lipid catabolism, the PPARα enhances the fatty acid oxidation during situations such as fasting, while PPARγ acts on the adipose tissue during the anabolic process to improve lipogenesis [54,55]. Thus, understanding the role of PPARs in energy homeostasis is important to further investigate the PPARs' role in producing energy in different body parts.…”
Section: Role Of Ppars and Coregulators In Energy Homeostasismentioning
confidence: 99%
“…The two most well-studied endocannabinoids are the arachidonic acid derivatives, N -arachidonoylethanolamine (AEA) and 2-arachidonoylglycerol (2-AG). We and others have shown that endocannabinoids can also act as potent anti-inflammatory agents [ 21 , 22 , 23 , 24 , 25 ]. Recently, we demonstrated that AEA can attenuate SEB-mediated ARDS in a mouse model by targeting miRNA which triggers anti-inflammatory pathways involving immunosuppressive cells, such as the myeloid-derived suppressor cells (MDSCs) and the regulatory T cells (Tregs) [ 9 ].…”
Section: Introductionmentioning
confidence: 99%